A SLM-molded titanium nail and a preparation method thereof

Through SLM molding and subsequent laser etching, pickling and alkaline heat treatment technologies, titanium nails with micro-nano multi-level structure and strong hydrophilicity were prepared, which solved the problem that titanium mesh and titanium nails were difficult to support and maintain space in the prior art, and improved the osteogenic effect during the GBR process.

CN116000317BActive Publication Date: 2025-04-25FOSHAN ANGELS BIOTECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310037260.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-09
Publication Date
2025-04-25
Estimated Expiration
2043-01-09

AI Technical Summary

Technical Problem

In the existing GBR technology, titanium mesh and titanium nails are difficult to support and maintain the space around the implant, easily fold and collapse, and the postoperative behavior leads to the displacement of bone meal, and the bone formation effect is not ideal.

Method used

Titanium nails with micron-scale structure were printed through SLM molding technology, and laser etching, pickling and alkaline heat treatment were performed to form titanium nails with micro-nano multi-level structure, low surface roughness and strong hydrophilicity.

Benefits of technology

It improves the biological activity and bone-promoting and differentiation ability of titanium nails, enhances the binding ability with bone, reduces the displacement and fall of the titanium mesh, and improves the osteogenic effect during GBR.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116000317B_ABST
    Figure CN116000317B_ABST
Patent Text Reader

Abstract

The invention discloses a SLM-molded titanium nail and a preparation method thereof, belonging to the technical field of biomedical implant metal materials; the preparation method of the SLM-molded titanium nail provided by the invention comprises titanium nail SLM molding, laser etching, pickling and alkaline heat treatment; the prepared SLM-molded titanium nail has both micron-nano multi-level structure and low surface roughness and strong hydrophilicity, which improves the biological activity of the surface of the SLM-molded titanium nail, strengthens its ability to promote bone differentiation and its ability to bind to bones, thereby making the SLM-molded titanium mesh not easy to displace, fall off and be exposed during the GBR process. In addition, the preparation method of the SLM-molded titanium nail provided by the invention is simple to operate, has low requirements on equipment, and is suitable for practical applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical implant metal materials, and in particular relates to a SLM-molded titanium nail and a preparation method thereof. Background Art

[0002] 3D printed medical products have promoted the continuous upgrading of medical technology in my country. In clinical treatment, digitalization has been combined to achieve a higher level of bone tissue replacement treatment. This involves the human body's limb bones, trunk bones, skull and teeth. In implant surgery, guided bone regeneration (GBR) technology uses bone scaffold materials and barrier membranes to eliminate the interference of tissue epithelium and connective tissue, promote osteoblast proliferation without interference, thereby increasing the bone mass of the alveolar ridge and preparing for the implantation of the later implant. Among them, titanium mesh is a very suitable scaffold material. Titanium mesh has a certain thickness, which is easy to cut and plastic, and has sufficient mechanical strength to control the contour of guided bone regeneration.

[0003] In the current GBR technology, the image data generated by the patient's oral cone beam CT (CBCT) and the three-dimensional surface STL data of the intraoral scan are first collected, and then the R&D engineer imports them into the guide design software for three-dimensional reconstruction, and designs the contour surface of the titanium mesh and the size, position and entry direction of the titanium nail according to the requirements of the attending physician, and then performs CAE simulation optimization design. Finally, the titanium mesh and titanium nails are formed by SLM.

[0004] At present, most GBR uses collagen membrane, while bone powder is a powdery substance that is difficult to support and maintain the space around the implant. It lacks the ability to form and may fold and collapse. The patient's talking, chewing and other behaviors after surgery can easily cause the displacement of bone powder, which ultimately leads to unsatisfactory osteogenesis. At the same time, when titanium mesh is used to assist osteogenesis, the titanium mesh is displaced, falls off and is exposed, resulting in unsatisfactory osteogenesis. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a SLM-molded titanium nail having a micron-nano multi-level structure and low roughness and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a SLM-formed titanium nail, the preparation method comprising the following steps:

[0007] (1) Titanium nail SLM molding: Using metal titanium powder as raw material, SLM molding 3D printing method is used to print SLM molded titanium nails with micron-level structure on the surface;

[0008] (2) Laser etching: laser etching the SLM-molded titanium nail obtained in step (1);

[0009] (3) Pickling: The SLM-molded titanium nail obtained in step (2) is placed in a 10-40% by mass hydrofluoric acid aqueous solution for cleaning for 1-6 seconds;

[0010] (4) Alkali heat treatment: The SLM-molded titanium nail obtained in step (3) is placed in an alkaline solution and heated to 100-120° C. and maintained for 4-6 hours. After the treatment, it is dried to obtain an SLM-molded titanium nail.

[0011] In a preparation method of an SLM formed titanium nail provided by the present invention, the printed SLM formed titanium nail with a surface micron-level structure is subsequently subjected to laser etching, pickling and alkaline heat treatment, and the pickling time and pickling solution as well as the temperature and time of the alkaline heat treatment are limited, so that the obtained SLM formed titanium nail can have a micron-nano multi-level structure and have low surface roughness and strong hydrophilicity, thereby improving the biological activity of the surface of the SLM formed titanium nail, enhancing its ability to promote bone differentiation and its ability to bind to bones, thereby preventing the SLM formed titanium mesh from being easily displaced, falling off and exposed during the GBR process. Specifically, through laser etching treatment, the surface of the SLM-molded titanium nail presents a micron-scale array concave hole structure, which increases the binding area and mechanical interlocking force with osteoblasts, is conducive to cell climbing and growth, improves biocompatibility, and promotes the adhesion and growth of osteoblasts; through acid pickling, the original oxide film of the SLM-molded titanium nail is removed and the micron surface is further roughened to provide a stable microenvironment for osteoblasts; through alkaline heat treatment, a nanometer-scale surface morphology is "grown" in the micron-scale porous array structure on the surface of the SLM-molded titanium nail, and the morphology is "three-dimensional mesh", which further reduces the roughness, and after alkaline heat treatment, a sodium titanate gel layer is formed on the surface of the SLM-molded titanium nail. Combined with the above-mentioned micron-nano structure, the microscopic morphology of the surface of the SLM-molded titanium nail is further effectively improved. At the same time, the alkaline heat treatment also provides a large number of hydroxyl groups for the surface of the SLM-molded titanium nail, which is hydrophilic and can absorb various protein components in the blood faster to promote bone integration.

[0012] As a preferred embodiment of the preparation method of the present invention, in the step (2), the parameters of laser etching are: speed of 0.4-0.6 mm / s, power of 14000-16000%, and frequency of 70 kHz.

[0013] As a preferred embodiment of the preparation method of the present invention, in the step (3), the pickling temperature is 22-28°C.

[0014] As a preferred embodiment of the preparation method of the present invention, in the step (3), the SLM-molded titanium nail obtained in the step (2) is placed in a hydrofluoric acid aqueous solution with a mass percentage of 10-20% for cleaning for 3-5 seconds.

[0015] As a preferred embodiment of the preparation method of the present invention, in the step (4), the alkali solution is a sodium hydroxide solution with a molar concentration of 4.5-5.5 mol / L.

[0016] As a preferred embodiment of the preparation method of the present invention, in the step (4), the SLM-molded titanium nail obtained in the step (3) is placed in an alkaline solution and heated to 110° C. and maintained for 4.5-5.5 hours.

[0017] As a preferred embodiment of the preparation method of the present invention, after each step, the obtained SLM-molded titanium nail is placed in acetone, 95% ethanol, and deionized water in turn for ultrasonic cleaning and drying.

[0018] The inventors have found that when the above preferred parameters are further adopted, the obtained product has lower roughness and stronger hydrophilicity.

[0019] In addition, the present invention also provides an SLM formed titanium nail, which is prepared by the preparation method of the present invention.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] In a method for preparing an SLM-molded titanium nail provided by the present invention, by performing subsequent laser etching, pickling and alkaline heat treatment on the printed SLM-molded titanium nail with a surface micron-level structure, the obtained SLM-molded titanium nail can have a micron-nano multi-level structure and low surface roughness and strong hydrophilicity, thereby improving the biological activity of the surface of the SLM-molded titanium nail, enhancing its ability to promote bone differentiation and its ability to bind to bones, thereby making the SLM-molded titanium mesh less likely to be displaced, detached and exposed during the GBR process. In addition, the method for preparing the SLM-molded titanium nail provided by the present invention is simple to operate, has low requirements on equipment, and is suitable for practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is an electron microscope image (10000X) of the SLM-formed titanium nail in Example 1 of the present invention;

[0023] Figure 2 This is an electron microscope image (10000X) of the SLM-formed titanium nail in Example 2 of the present invention;

[0024] Figure 3 This is an electron microscope image (2000X) of the SLM-formed titanium nail in Example 2 of the present invention;

[0025] Figure 4 This is an electron microscope image (10000X) of the SLM-formed titanium nail in Example 3 of the present invention;

[0026] Figure 5This is an electron microscope image (2000X) of the SLM-formed titanium nail in Example 3 of the present invention. DETAILED DESCRIPTION

[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0028] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0029] Example 1

[0030] An embodiment of the present invention provides a SLM formed titanium nail, and the preparation method of the SLM formed titanium nail comprises the following steps:

[0031] (1) SLM forming of titanium nails: The image data generated by the patient's oral cone beam CT (CBCT) and the three-dimensional surface STL data of the intraoral scan are collected and imported into the guide plate design software for three-dimensional reconstruction. The contour surface of the titanium mesh and the size, position and entry direction of the titanium nail are designed according to the requirements. CAE simulation optimization design is then performed to obtain the design drawing. Subsequently, based on the design drawing, SLM forming 3D printing is used to print SLM-molded titanium nails with a micron-level surface structure using metal titanium powder as raw material;

[0032] (2) Laser etching and cleaning: The surface of the SLM-molded titanium nail obtained in step (1) was laser etched, and the pulse laser parameters were: speed 0.5 mm / s, power 15000%, and frequency 70 kHz; after laser etching, the SLM-molded titanium nail was ultrasonically cleaned in acetone, 95% ethanol, and deionized water for 10 min respectively, and then taken out and dried;

[0033] (3) Pickling and cleaning: The SLM-molded titanium nail obtained in step (2) was placed in a pickling solution (40% by mass of hydrofluoric acid) and cleaned at 25° C. for 2 seconds; after pickling, the SLM-molded titanium nail was placed in acetone, 95% ethanol, and deionized water for ultrasonic cleaning for 10 minutes respectively, and then taken out and dried;

[0034] (4) Alkaline heat treatment and cleaning: The SLM-molded titanium nail obtained in step (3) is placed in a 5M sodium hydroxide aqueous solution, heated to 100° C. and maintained for 6 h. After the treatment, the SLM-molded titanium nail is placed in acetone, 95% ethanol, and deionized water for ultrasonic cleaning for 10 min respectively, and then taken out and dried to obtain the SLM-molded titanium nail;

[0035] The electron microscope image of the SLM-formed titanium nail is as follows: Figure 1 As shown, from Figure 1 It can be seen that the prepared SLM-formed titanium nail has a micron-nano multi-level structure and good microscopic morphology.

[0036] Example 2

[0037] An embodiment of the present invention provides a SLM formed titanium nail, and the preparation method of the SLM formed titanium nail comprises the following steps:

[0038] (1) SLM forming of titanium nails: The image data generated by the patient's oral cone beam CT (CBCT) and the three-dimensional surface STL data of the intraoral scan are collected and imported into the guide plate design software for three-dimensional reconstruction. The contour surface of the titanium mesh and the size, position and entry direction of the titanium nail are designed according to the requirements. CAE simulation optimization design is then performed to obtain the design drawing. Subsequently, based on the design drawing, SLM forming 3D printing is used to print SLM-molded titanium nails with a micron-level surface structure using metal titanium powder as raw material;

[0039] (2) Laser etching and cleaning: The surface of the SLM-molded titanium nail obtained in step (1) was laser etched, and the pulse laser parameters were: speed 0.5 mm / s, power 15000%, and frequency 70 kHz; after laser etching, the SLM-molded titanium nail was ultrasonically cleaned in acetone, 95% ethanol, and deionized water for 10 min respectively, and then taken out and dried;

[0040] (3) Pickling and cleaning: The SLM-molded titanium nail obtained in step (2) was placed in a pickling solution (30% by mass hydrofluoric acid) and cleaned at 25° C. for 2 seconds; after pickling, the SLM-molded titanium nail was placed in acetone, 95% ethanol, and deionized water for ultrasonic cleaning for 10 minutes respectively, and then taken out and dried;

[0041] (4) Alkaline heat treatment and cleaning: The SLM-molded titanium nail obtained in step (3) is placed in a 5M sodium hydroxide aqueous solution, heated to 120° C. and maintained for 4 h. After the treatment, the SLM-molded titanium nail is placed in acetone, 95% ethanol, and deionized water for ultrasonic cleaning for 10 min respectively, and then taken out and dried to obtain the SLM-molded titanium nail;

[0042] The electron microscope image of the SLM-formed titanium nail is as follows: Figure 2 and Figure 3 As shown, Figure 2 and Figure 3 The magnification is different and the size is also different, from Figure 2 and Figure 3 It can be seen that the prepared SLM-formed titanium nail has a micron-nano multi-level structure and good microscopic morphology.

[0043] Example 3

[0044] An embodiment of the present invention provides a SLM formed titanium nail, and the preparation method of the SLM formed titanium nail comprises the following steps:

[0045] (1) SLM forming of titanium nails: The image data generated by the patient's oral cone beam CT (CBCT) and the three-dimensional surface STL data of the intraoral scan are collected and imported into the guide plate design software for three-dimensional reconstruction. The contour surface of the titanium mesh and the size, position and entry direction of the titanium nail are designed according to the requirements. CAE simulation optimization design is then performed to obtain the design drawing. Subsequently, based on the design drawing, SLM forming 3D printing is used to print SLM-molded titanium nails with a micron-level surface structure using metal titanium powder as raw material;

[0046] (2) Laser etching and cleaning: The surface of the SLM-molded titanium nail obtained in step (1) was laser etched, and the pulse laser parameters were: speed 0.5 mm / s, power 15000%, and frequency 70 kHz; after laser etching, the SLM-molded titanium nail was ultrasonically cleaned in acetone, 95% ethanol, and deionized water for 10 min respectively, and then taken out and dried;

[0047] (3) Pickling and cleaning: The SLM-molded titanium nail obtained in step (2) was placed in a pickling solution (hydrofluoric acid with a mass percentage of 13%) and cleaned at 25° C. for 5 seconds; after pickling, the SLM-molded titanium nail was placed in acetone, 95% ethanol, and deionized water for ultrasonic cleaning for 10 minutes respectively, and then taken out and dried;

[0048] (4) Alkaline heat treatment and cleaning: The SLM-molded titanium nail obtained in step (3) is placed in a 5M sodium hydroxide aqueous solution, heated to 110° C. and maintained for 5 h. After the treatment, the SLM-molded titanium nail is placed in acetone, 95% ethanol, and deionized water for ultrasonic cleaning for 10 min respectively, and then taken out and dried to obtain the SLM-molded titanium nail;

[0049] The electron microscope image of the SLM-formed titanium nail is as follows: Figure 3 and Figure 5 As shown, Figure 4 and Figure 5 The magnification is different and the size is also different, from Figure 4 and Figure 5 It can be seen that the prepared SLM-formed titanium nail has a micron-nano multi-level structure and good microscopic morphology.

[0050] Comparative Example 1

[0051] The comparative example of the present invention provides an SLM formed titanium nail. The only difference between the preparation method of the SLM formed titanium nail and that of Example 1 is that in step (3), the pickling time is 10 s.

[0052] Comparative Example 2

[0053] The comparative example of the present invention provides an SLM formed titanium nail. The only difference between the preparation method of the SLM formed titanium nail and that of Example 1 is that in step (3), the mass percentage of hydrofluoric acid is 5%.

[0054] Comparative Example 3

[0055] The embodiment of the present invention provides an SLM formed titanium nail. The only difference between the preparation method of the SLM formed titanium nail and that of Example 1 is that in step (4), the temperature of the alkali heat treatment is 90°C.

[0056] Comparative Example 4

[0057] The embodiment of the present invention provides an SLM formed titanium nail. The only difference between the preparation method of the SLM formed titanium nail and that of Example 1 is that in step (4), the temperature of the alkali heat treatment is 130°C.

[0058] Effect example

[0059] Effect Examples of the Invention The surface roughness and contact angle of the products obtained in Examples 1-3 and Comparative Examples 1-4 were tested, wherein the roughness was tested using a surface roughness meter, and the contact angle was tested using a contact angle tester; the test results are shown in Table 1;

[0060] Table 1

[0061]

[0062]

[0063] It can be seen from Table 1 that when the method of the present invention is used, the obtained product has a low roughness and excellent hydrophilicity. Specifically, the obtained roughness value is below 3.56 um and the contact angle is below 7.1°;

[0064] It can be seen from Example 1 and Comparative Example 1 that when the pickling time is too long, it will cause slightly corroded small holes on the surface of the substrate, and the three-dimensional network structure "grown" near the small holes generated in the pickling process during the subsequent alkali heat treatment will be too dense, so that the roughness of the obtained product is significantly increased and the hydrophilicity is decreasing. Compared with Example 1, the roughness in Comparative Example 1 increases by 75% and the contact angle increases by 73%. It can be seen from Example 1 and Comparative Example 2 that when the mass percentage of hydrofluoric acid is too low, the oxide film will be removed unevenly, resulting in uneven "growth" during the subsequent alkali heat treatment. The roughness of the obtained product shows an increasing trend while the hydrophilicity shows a decreasing trend. Compared with Example 1, the roughness increases by 62% and the contact angle increases by 90%. It can be seen from Example 1 and Comparative Example 3 that when the temperature during the alkali heat treatment is too low, the roughness of the obtained product will also show an increasing trend while the hydrophilicity shows a decreasing trend. Compared with Example 1, the increase in the contact angle is 117%. It can be seen from Example 1 and Comparative Example 4 that when the temperature during the alkali heat treatment is too high, the roughness of the product will increase and the hydrophilicity will decrease.

[0065] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a SLM-molded titanium nail, characterized in that: The preparation method comprises the following steps: (1) Titanium nail SLM molding: Using metal titanium powder as raw material, SLM molding 3D printing method is used to print SLM molded titanium nails with micron-level structure on the surface; (2) Laser etching: The SLM-molded titanium nail obtained in step (1) is subjected to laser etching; the parameters of the laser etching are: speed of 0.4-0.6 mm / s, power of 14000-16000%, and frequency of 70 kHz; (3) Pickling: The SLM-molded titanium nail obtained in step (2) is placed in a 10-40% by mass hydrofluoric acid aqueous solution for cleaning for 1-6 seconds at a pickling temperature of 22-28° C. (4) Alkali heat treatment: placing the SLM-molded titanium nail obtained in step (3) in an alkali solution and heating it to 100-120° C. for 4-6 hours, and drying it after the treatment to obtain an SLM-molded titanium nail; In the step (4), the alkali solution is a sodium hydroxide solution with a molar concentration of 4.5-5.5 mol / L.

2. The preparation method according to claim 1, characterized in that: In the step (3), the SLM-molded titanium nail obtained in the step (2) is placed in a hydrofluoric acid aqueous solution with a mass percentage of 10-20% for cleaning for 3-5 seconds.

3. The preparation method according to claim 1, characterized in that: In the step (4), the SLM-molded titanium nail obtained in the step (3) is placed in an alkaline solution and heated to 110° C. and maintained for 4.5-5.5 hours.

4. The preparation method according to claim 1, characterized in that: After each step, the obtained SLM-molded titanium nails were placed in acetone, 95% ethanol, and deionized water for ultrasonic cleaning and drying.

5. A SLM-molded titanium nail, characterized in that: The SLM-molded titanium nail is prepared by the preparation method described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Method for preparing micro-nano composite structure on surface of medical titanium or titanium alloy

    CN102732898A

  • Surface treatment method for SLM molded titanium implant

    CN105537589A

  • Construction method for micro-nano hierarchical structure on surface of SLM forming titanium implant

    CN105689709A

  • Preparation method of titanium alloy bionic super-hydrophobic surface

    CN113278958A